The Impacts of Selecting Various Industrial Competitors on the Risk Level of Viet Nam Hardware Industry during and After the Global Crisis - Duc Nhuan, Nguyen; Tran Ngoc Huy, Dinh; Thi Phuong Thanh, Nguyen; Minh Dat, Pham (International Journal of Psychosocial Rehabilitation, 2020)
Using a one-factor model, this paperwork estimates the impacts of the size of firms’ competitors in the hardware industry on the market risk level, measured by equity and asset beta, of 22 listed companies in this category. This study identified that the risk dispersion level in this sample study could be minimized in case the competitor size doubles (measured by equity beta var of 0.678). Besides, the empirical research findings show us that the asset beta min value decreases from 0.054 to 0.030 when the size of the competitor doubles. Last but not least, most of the beta values are acceptable. Ultimately, this paper illustrates calculated results that might give proper recommendations to relevant governments and institutions in re-evaluating their policies during and after the financial crisis of 2007-2011.